Fusion detection in cancer (n = 613). - Shinsuke Suzuki (431254) (2025)
Kinase-related gene fusion and point mutations play pivotal roles as drivers in cancer, necessitating optimized, targeted therapy against these alterations. The efficacy of molecularly targeted therapeutics varies depending on the specific alteration, with great success reported for such therapeutics in the treatment of cancer with kinase fusion proteins. However, the involvement of actionable alterations in solid tumors, especially regarding kinase fusions, remains unclear. Therefore, in this study, we aimed to compare the number of actionable alterations in patients with tyrosine or serine/threonine kinase domain fusions, mutations, and copy number alterations (CNAs). We analyzed 613 patients with 40 solid cancer types who visited our division between June 2020 and April 2024. Furthermore, to detect alterations involving multiple-fusion calling, we performed comprehensive genomic sequencing using FoundationOne® companion diagnostic (F1CDx) and FoundationOne® Liquid companion diagnostic (F1LCDx). Patient characteristics and genomic profiles were analyzed to assess the frequency and distribution of actionable alterations across different cancer types. Notably, 44 of the 613 patients had fusions involving kinases, transcriptional regulators, or tumor suppressors. F1CDx and F1LCDx detected 13 cases with kinase-domain fusions. We identified 117 patients with kinase-domain mutations and 58 with kinase-domain CNAs. The number of actionable alterations in patients with kinase-domain fusion, mutation, or CNA (median [interquartile range; IQR]) was 2 (1–3), 5 (3–7), and 6 (4–8), respectively. Patients with kinase fusion had significantly fewer actionable alterations than those with kinase-domain mutations and CNAs. However, those with fusion involving tumor suppressors tended to have more actionable alterations (median [IQR]; 4 [2–9]). Cancers with kinase fusions exhibited fewer actionable alterations than those with kinase mutations and CNAs. These findings underscore the importance of detecting kinase alterations and indicate the pivotal role of kinase fusions as strong drivers of cancer development, highlighting their potential as prime targets for molecular therapeutics.